Lymphocyte-Specific Compensation For XLF/Cernunnos End-Joining Functions In V(D)J Recombination - Li, Gang (2008)
Mutations in XLF/Cernunnos (hereafter called "XLF") cause lymphocytopenia in humans, and various studies suggest an XLF role in classical non-homologous end joining (C-NHEJ). We now find that XLF-deficient mouse embryonic fibroblasts are ionizing radiation (IR) sensitive and severely impaired for ability to support V(D)J recombination. Yet, mature lymphocyte numbers in XLF-deficient mice are only modestly decreased. Moreover, XLF-deficient pro-B lines, while IR-sensitive, carry out V(D)J recombination at nearly wild-type levels. Correspondingly, XLF/p53-double-deficient mice are not markedly prone to the pro-B lymphomas that occur in previously characterized C-NHEJ/p53-deficient mice; however, like other C-NHEJ/p53-deficient mice they still develop medulloblastomas. Despite nearly normal V(D)J recombination in developing B cells, XLF-deficient mature B cells are moderately defective for IgH class switch recombination. Together, our results implicate XLF as a C-NHEJ factor, but also indicate that developing mouse lymphocytes harbor cell type specific factors/pathways that compensate for absence of XLF function during V(D)J recombination.